Gross Anatomical Study on the Mandible of Blue Bull (Boselaphus tragocamelus) - Bharti, Sanjay Kumar (Indian Journal of Veterinary Anatomy, 2020)
The present study was designed to provide the morphological characteristics of the mandible of blue bull. The paired mandible was made up of two similar halves, united with immovable articulation forming mandibular symphysis. The lingual sur-face was smooth and concave. The articular area of the mandible was rough and irregular. The most prominent part of the curve of the ramus formed the angle of the jaw; the part of the ramus between the body and the angle was called the horizontal part and carried the lower cheek teeth. Thepart of the ramus above the angle was termed the vertical part.Each ramus presented for description two surfaces, two borders and two extremities. The lateral surface was wider at the angle and narrower towards the extremities.